Sustainable Financing Initiatives and Bank Performance : A Bibliometric Analysis - Singh, Amit Kumar; Shrivastav, Rohit Kumar; Chapagain, Ramkrishna (Indian Journal of Finance, 2024)
Purpose : A comprehensive examination of current developments in sustainability and bank performance has been necessitated by the increased attention that governments, regulators, and policymakers are giving to the environment, climate change, and sustainability. The paper aimed to conduct a bibliometric analysis of sustainable financing and banking performance and suggest a future research agenda. Methodology : The study examined the well-known authors, journals, publications, and nations in sustainability and bank performance based on a bibliometric analysis of scientific papers obtained from the Web of Science and Scopus databases from 1989 to March 2023 using Vosviewer and Biblioshiny software. Findings : The study concluded that sustainable financing and banking performance is an emerging research area. The review revealed that China was the most productive country in terms of publication. The review further showed that the research interest had expanded in developing countries from developed countries with huge collaboration opportunities. Additionally, green investment, credit, and innovation were more popular in recent research areas. The Sustainability Journal was a prominent journal in the area studied. Practical Implications : The study served as a reference guide for managers, regulators, a concrete framework of recent trends and developments on sustainability and bank governments and academicians in their respective fields, as the research findings provided performance. Originality : This is the first bibliometric study that, as far as we know, has identified contemporary patterns in bank performance and sustainability. In a similar vein, this study generated significant subjects regarding sustainability and bank performance by employing science mapping to track present trends and developments.